The Great Mistake: How We Wrecked Public Universities and How We Can Fix Them By Christopher Newfield - Chinn, Sarah E. (Radical Teacher, 2017)
A review of a new book that examines the privatization of public higher education, how it happened, what it means, and how to counter it.